Innate immunity in the genitourinary tract: genetics of susceptibility to disease or asymptomatic carriage - Svanborg, Catharina (Henry Stewart Talks, 2012)
Pathogens\Commensals at the mucosal level, How pathogenic bacteria activate a host response, Pathogen specific innate immune signaling, Urinary tract infections (UTI), Uropathogenic E. coli vs. ABU strains, TLR4, CXCR1, IRF3, IL8R role in UTI response, Importance of identifying signaling pathways & crucial effector cells, Acute/Chronic pyelonephritis & asymptomatic bacteriuria, Genetics & UTI, Researching disease-associated polymorphisms, SNPs and their effect in APN & UTI, Mutations in structural genes, Response to infection in reporter assays, Commensalism vs. Virulence